Antioxidant Potential of Calophyllum gracilentum : A Study on Total Phenolic Content, Total Flavonoid Content, and Free Radical Scavenging Activities - Nurr Maria, Ulfa Seruji; Vivian Jong, Yi Mian; Nor Hisam, Zamakshshari; Thiruventhan, Karunakaran; Lee, Feng Koo; Wong, Tze Jin; Chan, Thye Huat (Eman Research Publishing, 2023)
The most prevalent phytoconstituents of medicinal and aromatic plants are phenols and flavonoids, which are responsible for antioxidant activity. This study aims to determine the total phenolic content (TPC), total flavonoid content (TFC), and free radical scavenging activity of Calophyllum gracilentum, an understudied Calophyllum species with very limited information. The stem bark extracts were prepared and examined for TPC assay by Folin–Ciocalteu method, while the TFC of the extracts was determined using aluminium chloride colorimetric method and the antioxidant activity was evaluated by free radical scavenging activity using 1,2-diphenyl-2-pricrylhydrazyl (DPPH). The extracts showed methanolic extracts exhibited the highest TPC and TFC with the value of 1542.40 ± 0.0246 mg GAE/g extract and 451.70 ± 0.0003 mg quercetin equivalents (QE)/g extract, respectively. Meanwhile, DPPH scavenging activity data revealed that all extracts had IC50 values ranging from 44.17 1.26 g/mL to 162.61 2.24 g/mL, with the methanolic extract for C. gracilentum having the highest antioxidant activity with IC50 values of 44.17 1.26 g/mL. The TPC and TFC assays showed that C. gracilentum extracts possess a substantial to moderate phenolic and flavonoid content, while the DPPH free radical scavenging assay revealed that the extracts have strong antioxidant activity. The results demonstrate that C. gracilentum contains a high concentration of phenolic and flavonoid chemicals. These discoveries could have significant implications for the prospective use of these plants in traditional medicine and as natural antioxidant sources.